(untitled) (Journal of Enam Medical College, 2017)
Voiding dysfunction and lower urinary tract symptoms (LUTS) in children due to congenital anomalies of urogenital system is common, but congenital anterior urethral diverticulum (CAUD) in male is very rare. Sometimes the problem is associated with anterior urethral valve. CAUD with secondary stone is rare. Here we report a case of a 12-year-old male child with obstructive symptoms. It was treated by excision of diverticulum, removal of stone and primary repair. J Enam Med Col 2017; 7(3): 162-164